PRAKTIK AUDIT SYARIAH DI LEMBAGA KEUANGAN SYARIAH INDONESIA - Qonita Mardiyah; Sepky Mardiyah (Akuntabilitas, 2015)
Islamic financial institutions (IFIs) have grown rapidly since the last few years.It raises the issue of shariah compliance in IFIs and the need for a new audit function,shariah audit. It’s functions to ensure accountability of financial statements prepared bymanagement and also ensuring shariah aspects are met perfectly by IFIs. Because if there isa failure in the implementation of shariah complience, stakeholders will loss their trust inthe IFIs even Islam itself. Therefore, this study will discuss about the current practice ofaudit shariah in Indonesia. the discussion of shariah auditing practices are focused on fourmain issues shariah audit, i.e the framework, scope, qualifications and independence ofauditors of sharia. This study was conducted using a survey method, in the form ofquestionnaires that measured with a likert scale to the three groups of respondents (SSBand internal auditors; external auditors, accounting academicians). These studies suggestthat the audit practice of sharia in Indonesia has been going well.DOI: 10.15408/akt.v8i1.2758